1981
DOI: 10.1073/pnas.78.4.2625
|View full text |Cite
|
Sign up to set email alerts
|

Neurite outgrowth from embryonic chicken spinal neurons is promoted by media conditioned by muscle cells.

Abstract: The effect of media conditioned by muscle cells on the development in vitro ofchicken spinal neurons was studied. Neural tube cells of 4.5-day chicken embryos were dissociated after trypsinization and cultured in serum-free minimum essential medium conditioned for 4 days over cultures of fused chicken myotubes. After 20 hr in conditioned medium (protein concentration, 10-50 ftg/ml), about 50% of surviving cells had extended neurites, whereas in cultures in nonconditioned medium this value was about 10%. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 19 publications
(15 reference statements)
2
41
0
Order By: Relevance
“…Release of trophic factors from the presynaptic nerve terminals may regulate the distribution and the ion-conducting properties of transmitter receptors in the postsynaptic membrane (Usdin & Fishbach, 1986;Nitkin et al, 1987;Laufer & Changeux, 1987;Mulle et al, 1988). Factors secreted by the postsynaptic cell may regulate the growth and survival of presynaptic neurones (Henderson et al, 1981;Gurney, 1984;Oppenheim & Haverkamp, 1988). It is now widely recognized that many mature neurones contain more than one neurotransmitter (Hokfelt et al, 1984), and in at least some instances, both substances have physiological effects on the postsynaptic cell (see, for example, Jan et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Release of trophic factors from the presynaptic nerve terminals may regulate the distribution and the ion-conducting properties of transmitter receptors in the postsynaptic membrane (Usdin & Fishbach, 1986;Nitkin et al, 1987;Laufer & Changeux, 1987;Mulle et al, 1988). Factors secreted by the postsynaptic cell may regulate the growth and survival of presynaptic neurones (Henderson et al, 1981;Gurney, 1984;Oppenheim & Haverkamp, 1988). It is now widely recognized that many mature neurones contain more than one neurotransmitter (Hokfelt et al, 1984), and in at least some instances, both substances have physiological effects on the postsynaptic cell (see, for example, Jan et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…For example it has been shown that cells dissociated from early embryonie chick, rat, or mouse spinal cords can be maintained in culture, and that media taken from cultured muscle cells or soluble extracts of muscle tissue increased the Ievels of cell survival, neurite outgrowth, and/or transmitter synthesis (see, e.g., Giller et aL, 1977;Bennett et aL, 1980;Brookes et aL, 1980;Godfrey et aL, 1980;Henderson et al, 1981;Longo et aL, 1982;Tanaka and Obata, 1982;Tanaka and Obata, 1983;Smith and Appel, 1983;Kaufman et al, 1985;Smith et aL, 1985). The fact, however, that motor neurons were not separated from other spinal cells makes the interpretation of these results ambiguous because it is not possible to decide whether the observed effects result from a direct action on the neurons in question or an indirect effect via other neuronal or nonneuronal cells (see Fukada, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of muscle cells, or medium conditioned by muscle cells, has been shown to affect several aspects of the development of cultured spinal cord cells. These include survival (Bennett et al, 1980), neurite outgrowth (Dribin and Barrett, 1980;Henderson et al, 1981), and neurotransmitter synthesis and metabolism (Giller et ab, 1977;Godfrey et al, 1980;Brookes et ak, 1980). However, in studies using whole spinal cord cultures, it is impossible to distinguish effects on motoneurons from effects on other classes of spinal cord cells.…”
Section: Introductionmentioning
confidence: 99%